+0  
 
0
199
1
avatar

if y=3x and 4x - 2y=5, then x = ?

Guest May 17, 2017
Sort: 

1+0 Answers

 #1
avatar+79894 
+1

y = 3x      (1)

 

4x - 2y  =  5       (2)

 

Sub (1)  into (2)   and we have

 

4x - 2 (3x)  =  5    simplify

 

4x - 6x   = 5

 

-2x  =  5        divide both sides by -2

 

x  =   -5 / 2

 

 

cool cool cool

CPhill  May 17, 2017

12 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details